Healing Effect of a Nano-Functionalized Medical-Grade Honey for the Treatment of Infected Wounds - Jessica Salvo; Cristian Sandoval; Carolina Schencke; Francisca Acevedo; Mariano del Sol (MDPI AG, 2023)
Based on the qualities of Ulmo honey (Eucryphia cordifolia), a medical-grade honey (Ulmoplus®) has been developed. Relevant to this, the use of copper represents an emerging therapy for the treatment of wounds. Therefore, the aim of this study was to see how this medical-grade honey with copper nanoparticles (CuNPs) helped to heal infected or non-infected wounds. Twenty-four guinea pigs (Cavia porcellus) were divided into four groups for phase 1 (without and with infection, U + F1 and U + F2), and two groups for phase 2 (selected formulation, without and with infection, U + F2NI and U + F2I). Bacteriological and histopathological studies, collagen fibers content evaluation, and stereological analysis were performed. The selected formulation displayed the same antibacterial potency as Ulmoplus®, indicating that this medical-grade honey by itself can be used as an antibacterial agent. However, the evaluation of collagen content demonstrated a significant increase in fibroblast and type III collagen fibers for infected and uninfected groups, which correlated with the histopathological study. Therefore, it is correct to affirm that adding CuNPs to Ulmoplus® improved the maturation of collagen fibers. Finally, polymorphonuclear cells presented similar values between experimental groups, which would indicate that the formulation under study was able to regulate the inflammatory process despite their infectious condition.